Immune responses to a HSV-2 polynucleotide immunotherapy COR-1 in HSV-2 positive subjects: A randomized double blinded phase I/IIa trial - Chandra, Janin; Woo, Wai-Ping; Dutton, Julie L.; Xu, Yan; Li, Bo; Kinrade, Sally; Druce, Julian; Finlayson, Neil; Griffin, Paul; Laing, Kerry J.; Koelle, David M.; Frazer, Ian H. (PloS one, 2019)
Genital herpes simplex infection affects more than 500 million people worldwide. We have previously shown that COR-1, a therapeutic HSV-2 polynucleotide vaccine candidate, is safe and well tolerated in healthy subjects. Here, we present a single center double-blind placebo-controlled, randomized phase I/IIa trial of COR-1 in HSV-2 positive subjects in which we assessed safety and tolerability as primary endpoints, and immunogenicity and therapeutic efficacy as exploratory endpoints. Forty-four HSV-2+ subjects confirmed by positive serology or pathology, and positive qPCR during baseline shedding, with a recurrent genital HSV-2 history of at least 12 months including three to nine reported lesions in 12 months prior to screening, aged 18 to 50 years females and males with given written informed consent, were randomized into two groups. Three immunizations at 4-week intervals and one booster immunization at 6 months, each of 1 mg COR-1 DNA or placebo, were administered intradermally as two injections of 500 μg each to either one forearm or both forearms. No serious adverse events, life-threatening events or deaths occurred throughout the study. As expected, HSV-2 infected subjects displayed gD2-specific antibody titers prior to immunization. COR-1 was associated with a reduction in viral shedding after booster administration compared with baseline. This study confirms the previously demonstrated safety of COR-1 in humans and indicates a potential for use of COR-1 as a therapy to reduce viral shedding in HSV-2 infected subjects.